Legal Aspects Of Deposits As Credits Guarantee To Bank (Study At PT. Bank Danamon, Tbk) - Zaini Hafiz Hasibuan (Journal of Law Science, 2021)
In general, economic activity in Indonesia is related to the general public with funds, meaning that every implementation of development requires funds for the continuity of the development. So that funds are a driving force that has such a big influence for progress in all aspects of the fields in the overall life of the nation and state. Likewise, business actors, both individuals and business entities, in carrying out development or business activities will require large amounts of funds, in the sense that the amount exceeds the funds and capital they have. One of the efforts for capital or funds is through bank credit facilities. So, it is appropriate to be able to understand how the implementation of credit agreements, how the efforts made in disbursing credit. This research uses a normative juridical approach proposed by Soerjono Soekamto, is a research study that emphasizes the science of law and tries to examine the legal rules and norms that apply in the midst of society. From a research result, it is found that First, in general, the implementation of credit agreements with deposit guarantees at first, prospective debtors must apply for credit by filling out the form as provided by the bank and completing all the administration, then the bank the bank performs a credit analysis to assessing the ability and feasibility of the debtor applying for credit. Second, after the application is received by the bank, the bank then makes disbursement efforts by binding it by signing and signed by the debtor (credit applicant) a letter of agreement and other documents that must be filled in for the credit disbursement process.